2019
DOI: 10.29141/2218-5003-2019-10-4-5
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of financial sustainability of microfinance institutions in Pakistan

Abstract: Since Pakistan achieved independence, poverty has become one of the most important issues in the country, which can be reduced with the help of microfinance sector. Pakistani microfinance institutions (MFIs) are facing a decline in profitability which makes it difficult for them to survive. The current study aims to investigate the determinants affecting the financial performance, i.e. profitability and sustainability of microfinance institutions in Pakistan, as well as to establish if attaining profitability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 1 publication
3
19
0
1
Order By: Relevance
“…Prospective investors always want to know about returns on their investment. Investor return was employed in the studies of Moskowitz (1972) to measure the enterprise's financial performance and was then later used in many other studies (Cochran and Wood, 1984;Naz et al, 2019). Price per share was used as an investor return in Moskowitz (1972) studies, which was later found to be faulty.…”
Section: Investor Returnsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prospective investors always want to know about returns on their investment. Investor return was employed in the studies of Moskowitz (1972) to measure the enterprise's financial performance and was then later used in many other studies (Cochran and Wood, 1984;Naz et al, 2019). Price per share was used as an investor return in Moskowitz (1972) studies, which was later found to be faulty.…”
Section: Investor Returnsmentioning
confidence: 99%
“…The operational cost of MFIs is higher than other banks as these provide services to the unbanked at their doorstep (Naz et al, 2019). The MFIs have to perform this function to raise lowincome customers' income levels (Akram and Hussain, 2011).…”
Section: Operational Self-sustainabilitymentioning
confidence: 99%
See 3 more Smart Citations